An Optimized Packet Transfer through Wireless Network Using Age of Information - Chen, Joy Iong Zong (IRO Journal on Sustainable Wireless Systems, 2020)
The cost for sampling a packet from transmission and transmitting the updates of the status using the wireless channel changes depending on the Age of Information (AoI) constraints. If any error occurs during the process of transmission, the decision lies with the scheduling algorithm to either retransmit the packet or to sample the packet again. Either way, the cost will include both transmission as well as sampling costs. However the aspect of sampling a new packet because of the error will result in increasing the cost of the system. With time average AoI constraint, we have devised a novel optimization technique that uses time average cost. In order to tackle this issue, we propose a decision making algorithm that decides in slots. The proposed algorithm arrives at one of the three solutions based on optimization technique. Accordingly, the user can either remain silent or transmit the old pack or sample the new packet. With the use of simulation results, the optimum performance of the proposed work in terms of AoI and timer average cost is observed and recorded.
Keywords: Age of Information; sampling; transmitting; Scheduling algorithm